Literacy through graphic novels : an autobiographical journey of developing teaching identity - Maceyovski, Ellen (My University, 2014)
This study explored the writer’s growth as a literate person and her emerging identity as a teacher and describes personal and educational experiences that influenced her beliefs about teaching. There is particular emphasis on the comics medium as a continuing thread in the development of her teaching identity. An autobiographical graphic novella was created to demonstrate the reflective process, the effectiveness of the graphic medium, and personal teacher identity. Among the influences on her identity were gender, race, class, adolescent experiences, academic experiences in undergraduate, preservice teacher education and graduate school. Her findings include an understanding of how many factors throughout her life influenced both her literate and teacher identities. By understanding the factors that shape one’s identity, one can better understand and embrace one’s evolving identity as a teacher; this can result in ultimately more effective, and sometimes more passionate, teaching.
Keywords: Identity (Philosophical concept); Graphic novels in education; Literacy; Study and teaching (Secondary)